Marriage without wali’s consent: the paradigm shift in family structure of Pakistan - Mehmood, Muhammad Ifzal; Md Hashim, Noraini (2018)
In Islamic Law an-nikah is a civil contract. Thus, to fulfil a valid contract all the requisites (arkan an-nikah) should be fulfilled. Majority of Islamic jurists opined guardian (wali) is one of the pillar determining the validity of marriage. Nevertheless, the Hanafi sect view it as a mere condition for a marriage. In Pakistan, a precedent has been set in the Supreme Court case of Saima Waheed, where it was decided that an adult Muslim woman can marry without the consent of her guardian. The decision has opened a debate whether guardian is a pillar of contract or merely a condition. In order to comprehend the issue of wali’s consent, it is essential to discuss the purpose of a marriage contract itself. The paper will kick off with the importance of the wali’s consent under Islamic law, follows by the elaboration of the legal status of a marriage contract without consent of guardian in Pakistani law. Besides armchair research, interviews with respondents involving females being forced into marriage were carried out too. The findings from the interviews, indicate that marriage without wali’s consent has destructed the family structure and isolated the partners from the family and society. The paper ends with importance to adhere to guardian in a marriage and recommendations to safeguard family system.